Faktor-Faktor yang Berhubungan dengan Perilaku Pencegahan COVID-19 pada Pegawai Kantor Wilayah Kementerian Agama DKI Jakarta - Maulana, Auliya Saphira; Lubis, Siti Rahmah Hidayatullah; Laelasari, Ela; Hamzens, Muhammad Farid (Faculty of Health Sciences, Syarif Hidayatullah State Islamic University of Jakarta, 2023)
AbstractThe virus that causes Covid-19 continues to mutate, where the more opportunities the virus has to spread, the more opportunities there are for change. DKI Jakarta reports that more than 537 offices in DKI Jakarta have become Covid-19 clusters. Therefore, workers also have a major contribution to make in breaking the chain of transmission of Covid-19 by implementing preventive behaviors that have been recommended by the government. The purpose of this study was to determine the factors related to Covid-19 prevention behavior in employees of the Ministry of Religious Affairs Jakarta Regional Office. The study design of this research was cross sectional with random sampling technique. The number of respondents as many as 53 employees of the Ministry of Religious Affairs Jakarta Regional Office. Data analysis used univariate and bivariate. The results showed that there was a relationship between facilities and facilities (P = 0.004) and policies (P = 0.021) with Covid-19 prevention behavior in employees of the Ministry of Religious Affairs Jakarta Regional Office. Therefore, the authorities can evaluate the program, have a system of giving sanctions or rewards, provide isolation rooms when symptoms are found and distance markers in elevators, canteens, and workspaces.Keywords: Covid-19, Office workers, Prevention behavior